Analisis Pemikiran Islam Terhadap Perkembangan Sastra Indonesia: Kajian Historis Dan Kontemporer: DOI 10.58569/jies.v3i2.1135 - Tasya Meilani; Tazkia Zharifa Ramadhani; Rahma, Zakiyyah; Muhamad Parhan (Journal of Islamic Education Studies, 2025)
Religion and literature can be interconnected, there are many literary works that contain Islamic teachings with learning values ​​that are used as life guidelines, both explicitly and implicitly. This is certainly inseparable from Islamic thought that is present in literary works, either from the author himself or from other figures who have sufficient knowledge about Islam. This study analyzes Islamic thought on the development of Indonesian literature with historical and contemporary studies on how Islamic thought influences literary works and is integrated into literary works. The results of the analysis will be presented descriptively qualitatively by describing Islamic thought on the development of Indonesian literature through a historical explanation of literature in Islamic teachings and the development of literature in Indonesia.